Providing emotional support around the point of multiple sclerosis diagnosis (PrEliMS-2): A multiple single case series - Thompson, Bethany; das Nair, Roshan; Tickle, Anna; Evangelou, Nikos; Hall, Henrietta; Moghaddam, Nima (2023)
Introduction Multiple Sclerosis (MS) is a neurological, progressive disease, for which there is no known cure. The diagnosis period generates a range of difficult emotional responses. Support around this time is crucial to longer-term coping with the disease, however it is not currently part of national service provision. A recent feasibility randomised controlled trial (PrEliMS-1) investigated how to provide this support using an Acceptance and Commitment Therapy (ACT) informed intervention, delivered by MS Nurse Specialists. No signals of efficacy were found however interview data suggests not all aspects of the intervention could be delivered. Therefore, we aimed to address this issue by having a Trainee Clinical Psychologist (TCP) deliver the intervention. Specifically, we were interested in (a) signals of efficacy of the PrEliMS intervention for improving the psychological impact of MS, (b) understanding possible mechanisms of change, (c) comparing signals of efficacy with PrEliMS-1, and (d) exploring potential improvements.